“Lapel Pins for Suffering” in the System of Official Awards of the XX-XXI Centuries - I. S. Samokhin; E. P. Komarovskaya; A. V. Chernov; M. G. Sergeeva (Научный диалог, 2019)
The question of the place of phaleronyms (medals, crosses, orders, etc.) awarded to a person for the suffering he has experienced is considered in the system of official awards of the 20th - 21st centuries. For their designation, the author uses the term lapel pins for suffering . This group includes, first and foremost, wound lapel pins given during the period of hostilities (for military personnel and, what is much less common, civilians), as well as awards intended for former prisoners of war, prisoners of fascist camps and victims of terrorist acts. The relevance of the study is due to the establishment at the beginning of the XXI century of about 20 new “lapel pins for suffering” and the evolution of attitudes towards individual grief in society and the state, while emphasizing the possible connection of the second factor with the psychological heritage of the two world wars. The main source of research material is a historical review by M.V. Tsarenko. Turning to other sources is clarifying and complementary. The scientific novelty of the work lies in the classification of "lapel pins for suffering" and understanding of their special place in the award system. It is shown that the considered lapel pins are awarded to a person precisely for suffering, that is, they cannot be characterized as a specific form of reward for merit in the traditional sense.